The reflective conservatoire: Studies in music education - Odam, George; Bannan, Nicholas (Aldershot Ashgate, 2005)
Across the world, fundamental changes in the music profession are in progress, stimulating profound questioning of the values promoted by conservatoires and specialist music schools. Techniques and methods used in preparing young musicians for a life dedicated to the performance and creation of music are being re-examined. Few studies have been published that focus on the education and training of musicians at higher-education level. This collection of essays and studies opens to the public some of the debates taking place within one conservatoire. These, together with the accompanying DVD, provide a variety of evidence resulting from research and development activities by performer-teachers associated with the Guildhall School.